The case against meta-consent: not only do Ploug and Holm not answer it, they make it even stronger. Issue 9 (6th December 2019) - Manson, Neil C
Abstract : In a recent article, I argued that Ploug and Holm's 'meta-consent' proposal should be rejected for biobank governance. This was because, although meta-consent is permissible, it is both burdensome and ethically omissible. There is no ethical reason why funders should undertake the additional costs. Ploug and Holm have sought to respond to these arguments. Here, it is noted that not only do they fail to adequately refuse the case against meta-consent, they fail to even engage with the arguments, either misunderstanding them or ignoring them. In their response, Ploug and Holm unwittingly provide the basis of an even stronger case against meta-consent. They argue that broad consent has a built in tendency to expire, while also holding that broad consent should be one of the options available in meta-consent. Meta-consent thus ends up being more like dynamic consent, but, arguably, even more burdensome and costly.